Microcredit and microentrepreneurship : collateral free loan at work in Bangladesh - Mondal, Wali I. (Dhaka : The Academic Press and Publishers, 2002)
Economics
2003-01-28
Keywords: Microcredit; Microentrepreneurship; Microfinance; Bangladesh